Exploring NK cell dynamics and the CD47-SIRPα axis in colon cancer - Yilmaz, Latif; Oztuzcu, Serdar; Eronat, Omer; Ugur, Berna Kaya; Gumus, Mahmut; Guler, Semih; Tasdemir, Demet; Bozgeyik, Esra; Caska, Halil; Bozgeyik, Ibrahim (Human immunology, 2025)
Inhibitory therapy targeting immune checkpoint regulators, specifically the SIRPα/CD47 axis, has emerged as a promising approach for cancer immunotherapy. SIRPα, which is predominantly expressed in neurons, dendritic cells, macrophages, and NK cells, inhibits professional phagocytes, primarily macrophages, from engulfing self-cells, including tumor cells, through its interaction with the self-recognition marker CD47. Targeting the CD47-SIRPα axis holds therapeutic promise for various cancers, including colorectal cancer. In the present study, we aimed to explore NK cell dynamics and the impact of the CD47/SIRPα axis in patients with colon cancer. We observed a dramatic, time-dependent decrease in NK cell numbers post-surgery, while IFNγ levels, which are indicative of NK cell activity, remained unchanged. Notably, IFNγ levels were significantly lower in patients than in healthy control subjects. In addition, tumors from colorectal cancer patients exhibited low CD47 immunoreactivity. Moreover, postoperative SIRPα levels in NK cells (CD16+/56+ and CD3−) were found to be significantly reduced in colon cancer patients in a gradual manner, regardless of CD47 status. Collectively, our findings reveal the multifaceted role of the CD47/SIRPα axis in colorectal cancer. However, further investigations with larger patient cohorts are warranted to validate these observations.